Fullerene stabilized gold nanoparticles supported on titanium dioxide for enhanced photocatalytic degradation of methyl orange and catalytic reduction of 4-nitrophenol. Issue 4 (August 2018) - Islam, Md. Tariqul; Jing, Hangkun; Yang, Ting; Zubia, Emmanuel; Goos, Alan G.; Bernal, Ricardo A.; Botez, Cristian E.; Narayan, Mahesh; Chan, Candace K.; Noveron, Juan C.
Graphical abstract: Fullerene Stabilized Gold Nanoparticles Supported on TiO2 for Enhanced Photocatalytic Degradation of Methyl Orange and the Catalytic Reduction of 4-nitrophenol. Highlights: Fullerene (C60 ) mediates the formation of gold nanoparticles (AuNPs). AuNPs bind to TiO2 without any surface functionalization. AuNPs-TiO2 enhances the photocatalytic degradation of methyl orange. AuNPs-TiO2 catalyzes the reduction of 4-nitrophenol to 4-aminophenol. AuNPs-TiO2 demonstrates high cyclic stability to the photocatalysis. Abstract: A facile method for the synthesis of gold nanoparticles (AuNPs) supported on TiO2 is reported. The average size of the TiO2 supported AuNPs was found to be about 8 nm, which was measured by the transmission electron microscopy. The TiO2 supported AuNPs exhibited enhanced photocatalytic degradation of methyl orange (MO) and catalytic reduction of 4-nitrophenol (4-NP) in water. Both the photocatalytic degradation of MO and the catalytic reduction of 4-NP were influenced by the size and the percent AuNPs loading. Compared to the pristine TiO2 the nanocomposite having 4.76 wt% AuNPs showed about twice and 132 times faster activity in the photodegradation of MO and the reduction of 4-NP, respectively The cyclic stability of the nanocomposite was examined for ten cycles and it was found that the catalyst is fairly active throughout the cycles. Further, the photocatalytic generation of hydroxyl radical (OH) was confirmed through the terephthalic acid photoluminescence tests.